The Global City versus the City of Neighborhoods: Spatial Practice, Cognitive Maps, and the Aesthetics of Urban Conflict. (June 2016) - Patterson, Matt
Political–economy, which conceptualizes space as a resource over which different groups struggle, has long been the dominant perspective in the study of urban conflict. However space is also a cultural object from which actors derive particular meanings. In order to understand how meaningful interpretations of space give rise to urban conflict, this paper examines the architectural expansions of two Toronto museums. Both projects were fiercely opposed by local creative and professional class residents—a group who might be expected to welcome elite architecture and cultural investment. To explain the origins of this conflict, I demonstrate how the museum leadership and surrounding community understood the spatial context of the expansion projects in strikingly different ways. While the former group saw Toronto as a "global city" and looked to international landmarks for precedents, the latter saw Toronto as a "city of neighborhoods" and were more concerned with how the projects contributed to more mundane aspects of the neighborhoods such as parks and playgrounds. I attribute these different "aesthetic" interpretations to the distinct spatial practices and associated cognitive maps of each group.